When a journalist decides to become a PR: an analysis of the role of university programmes and internships in Brazilian journalism students’ career choices - Pereira, Fabio Henrique (Estudios sobre el Mensaje Periodístico, 2015)
This paper analyses representations that Journalism undergraduate students at the University of Brasilia (UnB) make of public relations and corporate communication as a possible choice for their professional careers. It purposes a triangulation of the qualitative and quantitative data concerning student socialization processes. it analyzes: data obtained from a questionnaire administered to 119 UnB journalism undergraduates; journalism undergraduates’ reports on their 2012 internships; and indepth interviews conducted with five university teachers attached to the Journalism Department. The results show that right from the beginning of their course students perceive the career possibilities offered by the communication sector. Finally, this paper highlights the importance of the trainee/internship periods and of students’ interactions with the journalism teaching staff as spheres that tend to reinforce that representation of the labour market.